The awareness of Islamic financing among UiTM staff in Puncak Alam / Zuranashrin Mohd Kori - Mohd Kori, Zuranashrin (Academy of Contemporary Islamic Studies (ACIS), 2018)
The Asian Banker Research Group reported that the annual asset growth rate of the world‟s 100 largest Islamic banks is about 27 percent per annum, while the total global Islamic finance industry is growing at about 20 percent annually. However, there are several factors that become a barrier, making Islamic financing in Malaysia are not growing efficiently. We want to acknowledge if Malaysian‟s awareness in Islamic financing was the reason. Therefore, this research is conducted to identify the awareness of people about Islamic financing. Other than that, to acknowledge the implementation of Islamic financing in a research group and to determine people‟s knowledge about the differences of Islamic financing and conventional loan that has already spread in Malaysia. The method that is used in this research is by giving questionnaires among UiTM staff in Puncak Alam, Selangor. At the end of the findings, either the respondent‟s answer will answer the entire research question that is stated. Plus, some recommendations for improving the awareness about Islamic financing among Malaysian are being listed.